Teaching and Learning Signed Languages International Perspectives and Practices - McKee, David; Rosen, Russell S.; McKee, Rachel; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Teaching and Learning Signed Languages examines current practices, contexts, and the research nexus in the teaching and learning of signed languages, offering a contemporary, international survey of innovations in this field.
Keywords: Education; Sign language; Language and education; Teaching; Language and languages -- Study and teaching; Education; Language Teaching; Language Education; Learning & Instruction; Sign Language; Teaching and Teacher Education